The influence of acetylsalicylic acid on a condition of hepatocytes of pigs suffering from gastroenteritis - Шатохін, П. П.; Кравченко, С. О.; Канівець, Н. С.; Каришева, Л. П. (Scientific Progress & Innovations, 2016)
The publication presents data on the effect of acetylsalicylic acid («Aspirin») on the condition of hepatocytes in the treatment of pigs suffering from gastroenteritis. The activity of aspartate and alaninaminoransferaza of serum of weaned piglets, which are informative enzymes of metabolism in the liver, namely amino acid metabolism. It was found that the use of water-soluble «Aspirin» with therapeutic purposes for animals has not hepatotoxic action, unlike «Asglyukol», in the case of which application there is the destruction of hepatocytes, that is evidenced by hyperenzymemia AST and ALT.